2003
DOI: 10.1093/jnci/djg074
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Serologic Evidence for Prevalent Simian Virus 40 Infection in Humans

Abstract: These data indicate that some individuals have BKV and/or JCV antibodies that cross-react with SV40, but they do not provide support for SV40 being a prevalent human pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
103
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 26 publications
13
103
0
1
Order By: Relevance
“…46 Carter et al, using a VLP-based ELISA found 6.6% SV40 seroprevalence, but none of the positive reactions remained after competition with BKV or JCV VLP. 25 In accordance with this, in the present study only 5 positive samples remained when all previously positive samples and a selection of negative samples were retested in a neutralization assay, and none of these could neutralize SV40 when BKV/JCV was blocked.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…46 Carter et al, using a VLP-based ELISA found 6.6% SV40 seroprevalence, but none of the positive reactions remained after competition with BKV or JCV VLP. 25 In accordance with this, in the present study only 5 positive samples remained when all previously positive samples and a selection of negative samples were retested in a neutralization assay, and none of these could neutralize SV40 when BKV/JCV was blocked.…”
Section: Discussionsupporting
confidence: 70%
“…Recently published studies have shown that SV40 reactivity in human sera may be almost entirely a result of cross-reactivity with BKV and JCV antibodies. 24,25,46 Also in the present study, when SV40 VP1 antibodies were measured in the antibody capture assay without precautions to suppress crossreactive BKV and JCV VP1 antibodies they were correlated with BKV and/or JCV VP1 responses.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Contrasting reports have appeared in the literature on the presence of SV40 footprints in humans and its association with human tumors (20)(21)(22). SV40 antibody detection had been attempted in several studies using serologic methods with SV40 virus-like particles (VLPs), but because of high protein homology among the three main polyomaviruses SV40, BKV, and JCV, the results were always affected by some cross-reactivity (23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%